Inspection of Medical Devices For Regulatory Purposes - Badnjević, Almir; Cifrek, Mario; Magjarević, Ratko; Džemić, Zijad; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book offers all countries a guide to implementing verification systems for medical devices to ensure they satisfy their regulations. It describes the processes, procedures and need for integrating medical devices into the legal metrology framework, addresses their independent safety and performance verification, and highlights the associated savings for national healthcare systems, all with the ultimate goal of increasing the efficacy and reliability of patient diagnoses and treatment. The book primarily focuses on diagnostic and therapeutic medical devices, and reflects the latest international directives and regulations. Above all, the book demonstrates that integrating medical devices into the legal metrology system and establishing a fully operational national laboratory for the inspection of medical devices could significantly improve the reliability of medical devices in diagnosis and patient care, while also reducing costs for the healthcare system in the respective country.
Introduction -- Regulations and Directives - past, present, future -- Legal Metrology System - past, present, future -- Inspection of Diagnostic Medical Devices -- Inspection of Therapeutic Medical Devices -- Telemedicine Procedures -- Conclusion.
Keywords: Biomedical engineering; Measurement; Measuring instruments; Security systems; Biotechnology; Medical laws and legislation; Biomedical Engineering and Bioengineering; Measurement Science and Instrumentation; Security Science and Technology; Biotechnology; Medical Law